Antibiosis and Egg Parasitization in Root-Knot Nematode, Meloidogyne incognita by Indigenous Isolates of Trichoderma harzianum Rifai, 1969 in Relation to Chitinase and Protease Levels (Indian Journal of Nematology, 2019)
Among the thirteen native isolates of Trichoderma harzianum of Indian Type Culture Collection (ITCC) screened against the plant-parasitic nematode, Meloidogyne incognita, using the cell free extracts (CFF), the average antibiosis effect was the highest in ITCC 6888 leading to 97.30% mortality in infective juveniles (J2) .The egg masses incubated in the CFF for 20 days caused 99.50% egg hatch inhibition, compared to control. The attachment of spores and mycelia increased with an increase in days of incubation. The isolate was found to produce 51.42 U/mL of chitinase and 4.27U/mL of protease. On comparing the thirteen isolates of the fungal species, it was found that a level greater than 29U/mL resulted in egg parasitization, irrespective of protease levels.